1993
DOI: 10.3109/13813459309003918
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nifedipine and verapamil on rhythmic contractions of human isolated ureter

Abstract: The effect of calcium antagonists nifedipine and verapamil on spontaneous rhythmic contractions of human isolated ureter obtained from donor subjects undergoing kidney transplantation was investigated in comparison with a nonsteroidal antiinflammatory drug indomethacin. Stop-times i.e. the time elapsing from application, were determined for each drug. The rank order of potency at 10(-8) and 10(-7) M concentrations of the drugs was: nifedipine > verapamil > or = indomethacin. However, no significant difference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 12 publications
1
14
0
1
Order By: Relevance
“…24 Experiments using animal and human tissue models demonstrate that ureteric smooth muscle contraction can be stimulated by activation of adrenergic receptors, particularly the alpha-1D subtype. [25][26][27][28] Blockade of alpha-1 receptors by specific pharmacological antagonists (alpha-blockers) such as doxazosin, 29 terazosin, 30 alfuzosin 31 and, most typically, tamsulosin 32,33 results in ureteric smooth muscle relaxation. It was hypothesised that this would translate into clinical benefit for people with ureteric colic.…”
Section: Introductionmentioning
confidence: 99%
“…24 Experiments using animal and human tissue models demonstrate that ureteric smooth muscle contraction can be stimulated by activation of adrenergic receptors, particularly the alpha-1D subtype. [25][26][27][28] Blockade of alpha-1 receptors by specific pharmacological antagonists (alpha-blockers) such as doxazosin, 29 terazosin, 30 alfuzosin 31 and, most typically, tamsulosin 32,33 results in ureteric smooth muscle relaxation. It was hypothesised that this would translate into clinical benefit for people with ureteric colic.…”
Section: Introductionmentioning
confidence: 99%
“…Sahin et al [96] demonstrated that both endogenous PG synthesis and influx of calcium from the extracellular space is responsible for the spontaneous rhythmic activity of the ureter. Calcium-channel blocking drugs and steroids have been used to reduce ureteral tone and decrease inflammation in patients with ureteral stones [97] .…”
Section: Calcium Channel Blockersmentioning
confidence: 99%
“…Several studies have reported an increase in the rate of stone expulsion, shortened expulsion times and a decrease in analgesic consumption. [8][9][10][11] Tamsulosin, doxazosin, alfuzosin, silodosin, nifedipine and naftopidil are the most commonly used drugs in MET. 8,10,12 In this study, we compared the efficacy of tamsulosin and nifedipine in MET for distal ureteral stones in patients with renal colic.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Tamsulosin, doxazosin, alfuzosin, silodosin, nifedipine and naftopidil are the most commonly used drugs in MET. 8,10,12 In this study, we compared the efficacy of tamsulosin and nifedipine in MET for distal ureteral stones in patients with renal colic. In addition, during these treatment modalities, we evaluated the value of Hounsfield Unit (HU) of the stone detected in a non-contrast computerized tomography (NCCT) in the prediction of MET success rate.…”
Section: Introductionmentioning
confidence: 99%